A New Fixed Point Theorem and Applications - Min Fang; Xie Ping Ding (Abstract and Applied Analysis)
A new fixed point theorem is established under the setting of a generalized finitely continuous topological space (GFC-space) without the convexity structure. As applications, a weak KKM theorem and a minimax inequalities of Ky Fan type are also obtained under suitable conditions. Our results are different from known results in the literature.